Amplification of a metallacyclic receptor out of a dynamic combinatorial library. Issue 45 (6th November 2017) - Blanco-Gómez, Arturo; Rama, Tamara; Domarco, Olaya; Neira, Iago; Blanco, Víctor; Quintela, José M.; García, Marcos D.; Peinador, Carlos
Abstract : We present herein the Pt(ii )-directed self-assembly in water of a new conformationally flexible N -monoalkyl-4, 4-bipyridinium-based ditopic ligand into a library of six different metallacyclic structures. Abstract : We present herein the Pt(ii )-directed self-assembly in water of a new conformationally flexible N -monoalkyl-4, 4-bipyridinium-based ditopic ligand into a library of six different metallacyclic structures. This constitutionally dynamic library can be pushed to increase the production of one of the supramolecules in aqueous media, either by controlling the concentration of the building blocks or upon addition of an appropriate aromatic substrate.